Sowing of beans according to soil water availability in Northwest of Sao Paulo - Arroyo Avilez, Alberto Mario [UNESP]; Hernandez, Fernando Braz Tangerino [UNESP]; Bispo, Regiane de Carvalho [UNESP]; Castro Teixeira, Antonio Heriberto de (Univ Federal Reconcavo Bahia, 2018)
In order to recommend the best period for sowing of bean crop in the Itapura/SP region, the historical variables were analysed: rainfall distribution, evapotranspiration and soil water balance, comparing them with the data from 2017. In this way, the reference evapotranspiration was estimated by Penman-Monteith, and the corresponding crop coefficients (FAO 56) were applied, performing the daily water balance. Historically, the results indicate a better date for sowing on April 15, confirmed for the year 2017, with sowing in the second fortnight of March until the first fortnight of April. However, sowing from the month of May to August proved to be unfavorable.considering the water consumption by the plants and the occurrence/distribution of rainfall. The analysis of historical climatic variables proved to be an important tool for the definition of planting time considering the risks and operational costs related to bean production, as well as the question of planning the storage and use of water resources. recommended period allows the saving of 35% of the water applied, in addition to other agronomic advantages.
Keywords: Evapotranspiration; rainfall; water balance